Analysis of Brazilian industry’s dependency on imported inputs between 2000 and 2014 - Mortari, Valéria Silva (2019)
The aim of this paper is to analyse the extent to which different sectors of Brazilian industry were dependent on imported inputs between 2000 and 2014. The methodology of input-output analysis was used for this purpose, and the sectors were classified according to their direct and indirect demand for imported inputs. Sectors with relatively little demand for imported inputs are those related to the food, timber, wood and cork product industries and the repair and installation of machinery and equipment. The other industrial sectors relied on imported inputs to carry out their productive activities. The increasing use of imported inputs in Brazilian production processes means that the benefits of sector growth are partly appropriated by other economies.